Synergistic effect of extracellular polymeric substances and carbon layer on electron utilization of Fe@C during anaerobic treatment of refractory wastewater. (1st March 2023) - Xu, Hui; Zhang, Liang; Yao, Chunhong; Yang, Bo; Zhou, Yan
Highlights: Fe@C composites enhanced the anaerobic degradation of azo dye. The duration of bioaugmentation of Fe@C was greater than that of NZVI. Synergistic interactions between the carbon layer and EPS improved electron utilization. Intermittent dosage of Fe@C maintained the high expression of genes related to dye degradation. Abstract: Nano zero-valent iron (NZVI) has been widely used to improve refractory wastewater treatment. However, the rapid dissolution of NZVI causes a waste of resources and an unstable bioaugmentation. Herein, to verify the essential role of slow release of NZVI on biological systems, a core-shell structured Fe@C composite was developed to demonstrate the long-term feasibility of Fe@C for enhancing azo dye biodegradation in comparison to a mixture of NZVI and carbon powder (Fe+C). The 150 days of long-term reactor operation showed that, although both Fe@C and Fe+C enhanced azo dye degradation, the former achieved a better performance than the latter. The strengthening effect of Fe@C was also more durable and stable than Fe+C. It may be due to the fact that the carbon layer of Fe@C could interact with extracellular polymeric substances (EPS) through physical adsorption and chemical bonding to form a stable buffer to regulate NZVI dissolution. The buffer layer could not only regulate the attack of H + on NZVI to reduce its dissolution rate but also complex released Fe 2+ and neutralize OH − to alleviate the passivation layer formed on the NZVI surface. Moreover, microbial community analysis indicated that both Fe@C and Fe+C increased the abundance of fermentative bacteria ( e.g., Bacteroidetes_vadinHA17, Propionicicella ) and methanogens ( e.g., Methanobacterium ), but only Fe@C promoted the growth of azo dye degraders ( e.g., Clostridium, Geobacter ). Metatranscriptomic analysis further revealed that only Fe@C could substantially stimulate the expression of azoreductase and redox mediator ( e.g., riboflavin, ubiquinone) biosynthesis involved in the extracellular degradation of azo dye. This work provides novel insights into the bioaugmentation of Fe@C for refractory wastewater treatment. Graphical abstract: Image, graphical abstract